Building a Better Future for All - United Nations (United Nations, 2013)
The United Nations works across the world for peace, sustainable development, human rights and the rule of law. This collection of speeches by Secretary-General Ban Ki-moon shows the breadth of those efforts – advances and struggles alike – at a time of profound transition for the human family. Since taking office in 2007, Secretary-General Ban Ki-moon has sought to mobilize the international community behind global solutions to urgent challenges ranging from climate change and poverty to armed conflict and the spread of deadly weapons. The goal: dignity, freedom and opportunity for all.